A comparative method of viral and neural marketing, with a modern marketing approach - Safaei Mehdi, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
In today's competitive world, marketing as a dynamic, operational science is constantly evolving in line with developments. The critical role and importance of marketing strategies in the success or failure of organizations have become clear to everyone. Marketing and its strategies have been heavily influenced by technologies throughout their lives. With the advent of print, radio, television, computers, and so on, marketing has also played a specific role. The advent of information technology and the rapid growth of communications in cyberspace have completely revolutionized marketing strategies. In the meantime, in order to make companies successful in marketing, different strategies were introduced. The purpose of this study is to provide a comprehensive overview of Neuro-marketing and Viral-marketing while exploring the different aspects of these two marketing styles. Finally, according to the indices and characteristics obtained through field studies and library research, these two types of marketing will be analyzed. On the other hand, the role of the five senses (sight, hearing, smell, touch, and taste) in neural marketing will be examined. And it examines how each of these senses affects the customer's mood and overshadows his purchase. This will help sellers and marketers a lot more sales. The results suggest that the strategic stimulation of the consumer's five senses in the marketing process can be one of the practical ways for companies and sellers to attract customers and increase their loyalty.